Маркетплейс як дієвий інструмент цифрового маркетингу - Просович, О. П.; Боцман, Ю. С.; Prosovych, O.; Botsman, Y. (Видавництво Львівської політехніки, 2018)
Досліджено актуальність використання сучасних інструментів цифрового маркетингу, а саме: маркетплейсу. Дано характеристику поняттю “маркетплейс”, виділено його типи, основні особливості і переваги застосування. Висвітлення його основних переваг, недоліків та особливостей застосування для розвитку електронного бізнесу. Для цього доцільно оцінити сучасний стан розвитку інтернет-платформ на вітчизняному ринку та визначити їх можливості у перспективі. Маркетплейс є типом веб-платформи електронної комерції, яка допомагає продавцям та потенційним покупцям знаходити один одного в Інтернеті, а потім взаємодіяти. Така модель однаково актуальна і для продавців товарів, і для тих, хто пропонує послуги. Наведено класифікацію лідерів цифрового маркетингу на вітчизняному ринку за чотирма категоріями: інтернетмагазини, прайс-агрегатори, маркетплейси і класифайди. Маркетплейс створюється для великої кількості постачальників і споживачів. Учасники можуть взаємодіяти на рівних (коли обидві сторони – приватні особи або представники бізнесу). Оцінено сучасний стан та перспективи розвитку маркетплейсу та його лідерів в Україні. Маркетплейс – двостороння торгова площадка, що в рази ускладнює аналітику, тому потрібно розуміти, які показники вважати для сегмента продавців, а які для користувачів, крім того, постійно врівноважувати між собою попит і пропозицію.

In the article the relevance of using modern digital marketing tools, namely the marketplaces, is investigated. The description of the “markeplays” concept is given, its types, main features and advantages of application are highlighted. Describes its main advantages, disadvantages and features of application for the development of e-business. To this end, it is advisable to evaluate the current state of development ofInternet platforms on the domestic market and determine their potential in the future.A marketplace is a type of e-commerce web platform that helps sellers and potential buyers find each other online and then interact. Such a model of this web platform is relevant for sellers who provide goods as well as services. The main sources of income of the marketplays are determined depending on the conditions of cooperation. The classification of the leaders of digital marketing on the domestic market is presented in four categories: online-shops, price-aggregators, marketplays and classfiles. A marketplace is created to acquire and accommodate a huge amount of vendors and customers. Participants can interact as equals (when both sides are private individuals or business representatives) or develop a hierarchy “entrepreneur-client”. The distribution of traffic by type of platforms is analyzed. The current state and prospects of marketplaces development and its leaders in Ukraine are estimated. The main four strategies that use by marketplaces are successful in the market and are represented. The world tendencies of e-commerce development in recent years, including in Ukraine, are analyzed. Whilst growing a marketplace, founders need to keep an eye on the most important factors to calculate. As a twosided web platform, marketplace aggregates many sellers and their inventory on one website as well as a lot of buyers. Customers need supply, and sellers need customers, now we are going to concentrate on the analysis of the key performance indicators. The five key factors that contribute to the development of domestic e-commerce are highlighted.
Marketplace as a digital marketing tool
Keywords: маркетплейс; цифровий маркетинг; торговельний майданчик; e-commerce; електронний магазин; бізнес-модель; marketplaces; digital marketing; online trading; trading platform; ecommerce; business model; 339.138